(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
An investigation of the connection between adult aggressiveness and social intelligence was the goal of this study. This study was carried out using the descriptive-correlational research methodology. The current state of adult social intelligence and aggressiveness was described in a descriptive manner. The association between aggressiveness and social IQ was examined using the correlational approach. There were two hundred adults in the research population. A multistage cluster sampling technique was used to choose 100 subjects. Measurement instruments such as the aggressiveness questionnaire by Buss Perry (1992) and the social intelligence questionnaire by Thout (1995) were utilized to evaluate the individuals. Correlation and regression coefficients were employed in the analysis of the collected data. The findings indicated that social IQ and aggression particularly verbal, physical, violent, and hostile behavior among adults were significantly correlated. Additionally, the data demonstrated that aggressive conduct decreases with increasing adult social IQ. Therefore, in order to reduce the violent behaviours of adults, it is necessary to increase their social intelligence through curriculum preparation, in-service education programmes, and principal education seminars.